(untitled) (UNIZIK Journal of Marketing, 2024)
The study focuses on Evaluation of Artificial Intelligence and Efficacy of E-commerce adoption in Nigeria. Artificial Intelligence (AI) has become increasingly popular globally as a crucial tool for electronic marketing and commerce, but in Nigeria, the adoption and use of AI tools by marketers is still in its early stages. Attention has been primarily focused on the basic 5 popular e-commerce companies in Nigeria, with little attention given to small-scale online business practitioners in Nigeria. This study seeks to examine the impact of AI on electronic marketing and commerce adoption in Nigeria by employing a survey research design. The population of this study comprises 178 e-commerce firms operating in Lagos and Rivers State, with a sample size of 124 firms selected using purposive sampling technique. Data was collected through a well-structured questionnaire, and the reliability of the research instrument was confirmed with a Cronbach Alpha test result of an average of 70%. Descriptive analysis and regression analysis were used to analyse the data, and the results indicated that Ease of use, data mining, machine learning, and consistent messages across channels exhibited a significant positive relationship with e-commerce adoption rate in Nigeria. The study concluded that the use of AI will enable digital marketers to predict future trends and make more informed decisions that focus on improving online marketing offerings and encourage more people to participate in online marketing. The study recommended constant training of consumers and marketing personnel on the use of the online marketing interface, data mining techniques to improve e-commerce, investment in machine learning tools by e-marketing firms in Nigeria, and increased use of ease-of-use interface that will entice the consumers to purchase online and also break their normative belief that once anyone makes available their card information online, that he/she will be defrauded.